Climate data sonification and visualization: An analysis of topics, aesthetics, and characteristics in 32 recent projects - Lindborg, PerMagnus; Lenzi, Sara; Chen, Manni (Frontiers in Psychology, 2023)
It has proven a hard challenge to stimulate climate action with climate data. While scientists communicate through words, numbers, and diagrams, artists use movement, images, and sound. Sonification, the translation of data into sound, and visualisation, offer techniques for representing climate data with often innovative and exciting results. The concept of sonification was initially defined in terms of engineering, and while this view remains dominant, researchers increasingly make use of knowledge from electroacoustic music (EAM) to make sonifications more convincing. The Aesthetic Perspective Space (APS) is a two-dimensional model that bridges utilitarian-oriented sonification and music. We started with a review of 395 sonification projects, from which a corpus of 32 that target climate change was chosen; a subset of 18 also integrate visualisation of the data. To clarify relationships with climate data sources, we determined topics and subtopics in a hierarchical classification. Media duration and lexical diversity in descriptions were determined. We developed a protocol to span the APS dimensions, Intentionality and Indexicality, and evaluated its circumplexity. We constructed 25 scales to cover a range of qualitative characteristics applicable to sonification and sonification-visualisation projects, and through exploratory factor analysis, identified five essential aspects of the project descriptions, labelled Action, Technical, Context, Perspective, and Visualisation. Through linear regression modelling, we investigated the prediction of aesthetic perspective from essential aspects, media duration, and lexical diversity. Significant regressions across the corpus were identified for Perspective (ß = 0.41***) and lexical diversity (ß = -0.23*) on Intentionality, and for Perspective (ß = 0.36***) and Duration (logarithmic; ß = -0.25*) on Indexicality. We discuss how these relationships play out in specific projects, also within the corpus subset that integrated data visualisation, as well as broader implications of aesthetics on design techniques for multimodal representations aimed at conveying scientific data. Our approach is informed by the ongoing discussion in sound design and auditory perception research communities on the relationship between sonification and EAM. Through its analysis of topics, qualitative characteristics, and aesthetics across a range of projects, our study contributes to the development of empirically founded design techniques, applicable to climate science communication and other fields.